THE EFFECT OF COMPETENCE, INDEPENDENCE AND WORKLOAD ON AUDIT QUALITY - Didit Darmawan; Ella Anastaysa Sinambela; Nur Ika Mauliyah (Universitas Islam Balitar, 2016)
One indicator of quality actions in management and company is the assessment of financial reports through audit actions. In every audit action is always expected to give qualified results based on the conclusions and opinions objectively. The auditor becomes the prominant determinant of how the results of an audit action can be answerable. The competency, independency and workload become a causal variable of an auditor behavior ’s perspective on audit quality. The purpose of this study is analyzing and determining the effect of partial and simultaneous competency, independency, and workload on audit quality and knowing which independent variables which have a significant effect on audit quality. The study involved 66 respondents. Then the collected data is analyzed by multiple regression and using SPSS which has been tested by validity, reliability test, and classical assumption test. The results of this study proves that there is a positive and significant influence partially and simutaneously from a competency variable, independency and workload on audit quality. The independency becomes a dominant variable which influence audit quality. Keywords: audit quality; competency; independency; workload. Received: 10 August, 2017; Accepter: 10 September, 2017